Building a bright future: the educational alliance between the between UAN and the Piccolino Foundation (REVISTA SAYWA, 2024)
Education is a fundamental tool for the development of any society, and this is something that the Antonio Nariño University is very aware of. That is why, through its social outreach program, it has decided to provide biology, physics, chemistry and mathematics classes to the Piccolino Foundation, a non-profit organization dedicated to providing education to underprivileged youth and seniors.